Human Rights and the Citizen of the Kingdom of Heaven - Lau, Sean (The ecumenical review, 2019)
This article argues for a new Christian theological rationale for human rights that takes into account serious contemporary critiques of rights language. Human rights derive from our being made in the image of God. But rather than being static metaphysical properties which humanity possesses, they form a moral language about the image of God, which must be constantly refashioned to suit the times. Furthermore, the human community to which these rights belong is not mere created humanity, but instead the humanity of the eschatological kingdom of heaven, of which the ecumenical church is the messenger. The ecumenical task, then, is to articulate a more holistic conception of what the image of God means to ensure that human rights language does not become narrowly sectarian.